Research Progress on Corrosion of Equipment and Materials in Deep-Sea Environment. (3rd December 2021) - Chen, Sheng; Qiu, Liping; Sun, Shaofang; Yang, Junyi; Meng, Qinghua; Yang, Weibo
Abstract : The deep sea is the frontier of materials research in the 21st century. Owing to the particularity of pressure (15–120 MPa), hydrothermal temperature (90–400°C), and explosive fluid (strong H2 S) in the deep-sea hydrothermal field environment, the research on the corrosion mechanism of service materials in this environment under the coupling action of many harsh factors is almost blank. It has become the bottleneck of equipment and material research and development for China to explore the deep sea. This paper reviews the research progress of corrosion mechanisms of deep-sea environmental materials at home and abroad, and forecasts the research trend and difficulties in this field, especially in the deep-sea hydrothermal field. At the same time, it points out the urgency of the construction of harsh environment materials platform and its relevance to the discipline construction of marine college.